APPLICATION OF BLENDED LESSONS ON PRODUCTIVE COURSES OF CLASS XI VOCATIONAL SCHOOL - Mauludin, Harri Azhari; Komaro, Mumu (Universitas Pendidikan Indonesia, 2021)
The Covid-19 pandemic has affected various areas of life, including the education sector. The education sector is faced with adapting to new habits in the new normal era. Blended learning is an alternative learning in the current new normal era. This study aims to determine the achievement of productive learning in the new normal era with the blended learning method in aspects of school infrastructure readiness, teacher readiness and learning activities using this method. The survey method was used to obtain quantitative data by taking the population and sample of class XI of the Cooling and Air Conditioning Engineering Skills Program at SMKN 1 Cimahi as many as 70 students. Data collection techniques by distributing questionnaires and interviews. The results of the blended learning method are obtained as a solution for learning methods, especially for productive learning methods in this new normal era. The results of the aspect of infrastructure readiness in schools in preparing facilities and infrastructure related to the Covid-19 health protocol were obtained before learning activities began, with an interpretation score of 1718 which showed that it was in the good category. In addition, the aspect of teacher readiness in learning in the new normal era by using the blended learning method in terms of developing learning media, knowledge and competence, obtained an interpretation score of 1529 which showed it was in the good category. Furthermore, in the aspect of learning activities, students have high enthusiasm and make effective limited time in learning using the blended learning method, with an interpretation score of 1718 which shows this aspect in the good category. In conclusion, productive learning using blended learning learning methods in the new normal era makes practicum activities can be carried out properly and can achieve the specified target so that it has a good effect on improving student learning outcomes.